2021
DOI: 10.1016/j.amsu.2021.102710
|View full text |Cite
|
Sign up to set email alerts
|

Shock index as a prognosticator for emergent surgical intervention and mortality in trauma patients in Johannesburg: A retrospective cohort study

Abstract: Introduction Trauma is the leading cause of morbidity and mortality worldwide with exsanguination being the primary preventable cause through early surgical intervention. We assessed two popular trauma scoring systems, injury severity scores (ISS) and shock index (SI) to determine the optimal cut off values that may predict the need for emergent surgical intervention (ESI) and in-hospital mortality. Methods A retrospective analysis of patient records from a tertiary hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Several studies from the 1990s showed that patients undergoing diagnostic laparoscopy (DL) had a high rate of missed injury (41%) [ 7 , 11 ]. However, as laparoscopic instruments and expertise improve, the reported rates of missed injuries have decreased to as low as 0.12% [ 7 , 11 , 15 ]. This decline has been ascribed to the introduction of a systematic examination in trauma laparoscopy [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies from the 1990s showed that patients undergoing diagnostic laparoscopy (DL) had a high rate of missed injury (41%) [ 7 , 11 ]. However, as laparoscopic instruments and expertise improve, the reported rates of missed injuries have decreased to as low as 0.12% [ 7 , 11 , 15 ]. This decline has been ascribed to the introduction of a systematic examination in trauma laparoscopy [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…We see significant penetrating abdominal trauma in our institution [ 14 , 15 ]. The emergency workload further adds pressure on theatre availability time.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies show that the SI obtained by dividing the heart rate by the systemic blood pressure, which Allgower first described in 1976, is more reliable in determining trauma severity than that of hypotension and tachycardia alone. [ 11 , 12 , 23 25 ] Lammers et al[ 26 ] reported that SI and injury severity score (ISS) were similarly effective in predicting surgical necessity and mortality in patients with trauma. In addition, Inal et al[ 27 ] reported that SI effectively determines prognosis in patients followed up in the intensive care unit after emergency surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Richard Crawford et al reported that SI successfully predicted surgical necessity and mortality. [ 12 ] However, Shibahashi et al[ 10 ] found that the efficacy of SI was more limited in older patients and emphasized the SI modified for age. In addition, Il-Jae Wang et al[ 28 ] showed that SI (preSI) evaluated pre-hospital is effective in estimating mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation